2014
DOI: 10.3727/152599514x14143427352238
|View full text |Cite
|
Sign up to set email alerts
|

Managing Alcohol and Drugs in Event and Venue Settings: The Australian Case

Abstract: has resulted from the rising number of incidents of individual harm, violence, and community disruption that have occurred in and around these settings. This situation, in turn, has created a need to identify and better understand those factors with the potential to produce such negative outcomes, along with the practices that can be employed to minimize them. This study has been conducted in response to this need. This article begins by providing an overview of literature germane to: alcohol and drug use in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In particular, many injuries in public places occur on the way home after a night out, often in a drinking establishment [39]. Also, as a matter of routine, staff at drinking establishments will push incipient trouble, such as a noisy drunk or an intense argument or fight, out onto the street [40], motivated not only by avoiding disturbance of other customers but also by laws that an intoxicated person cannot stay in the bar, and by the threat to the establishment's license to sell alcohol if it has a record of fighting and trouble [41,42]. Our findings suggest attention in future studies to the location of drinking as well as of the injury, in studying the influence of location on the relationship between drinking and injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many injuries in public places occur on the way home after a night out, often in a drinking establishment [39]. Also, as a matter of routine, staff at drinking establishments will push incipient trouble, such as a noisy drunk or an intense argument or fight, out onto the street [40], motivated not only by avoiding disturbance of other customers but also by laws that an intoxicated person cannot stay in the bar, and by the threat to the establishment's license to sell alcohol if it has a record of fighting and trouble [41,42]. Our findings suggest attention in future studies to the location of drinking as well as of the injury, in studying the influence of location on the relationship between drinking and injury.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for non-medical use of psychotropic drugs are often multiple, but they can be grouped into three main categories: recreational use, self-medication, and performance enhancement, particularly at school [ 13 , 20 ]. The use of legal psychotropic substances, especially alcohol, has always been associated with partying [ 21 ], whether in a student or non-student setting, but drugs are also used in this context, either for their own effects or to enhance or counteract the effects of other substances [ 22 , 23 ]. With regard to self-medication, a study of university students in Norway found a significant association between psychological distress and the use of psychotropic drugs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%